STABILITAS NANOSTRUCTURED LIPID CARRIER COENZYME Q10 DENGAN VARIASI WAKTU PENGADUKAN - Usrifatul Khasanah; M Fatchur Rochman (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
Coenzyme Q10 (Co-Q10) or Ubiquinone is an antioxidant that is unstable to light and is highly lipophilic causing instability during storage, so a Nanostructured Lipid Carrier (NLC) delivery system is needed that can improve stability. The manufacture of NLC uses the emulsification method by melting two types of lipids, namely solid lipid cetyl palmitate and liquid lipid alpha tocopherol with the help of stirring using a magnetic stirrer. The purpose of this study was to determine the characteristics and stability of NLC Co-Q10 at various stirring times. The results of testing the characteristics NLC Co-Q10, that stirring for 6 and 9 minutes, obtained pH values of 6,64 and 6,62 with particle sizes of 215.03 nm and 188.25 nm, the entrapment efficiency values were 75.57% and 77.96%, respectively. Increasing the speed and duration of stirring in the manufacture of the NLC Co-Q10 system will obtain high trapping efficiency values and be more stable in storage at room temperature for 28 days.